Tuổi K-Ar, 40Ar/39Ar và vấn đề tuổi Proterozoi sớm của Horblen Hưng Khánh - Nam, Trần Ngọc; Thắng, Tạ Trọng (Vietnam Journal of Earth Sciences, 2000)
K-Ar, 40Ar/39Ar ages and problem of earlvProterozoic age of Hung Kiranh hornblenies